Value orientation and reflectivity of personality as factors of influence on the gifted young people - Anastatia Polishchuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article highlights the issues of giftedness of the individual. The content of the notion "giftedness" was clarified in the context of the selected study areas, namely academic activities of students in secondary school with technical direction and also members and residents of the MAN of Ukraine. The research subject was chosen as the value orientation and reflectivity of personality as factors of influence on the gifted young people. Interaction between leading activity of adolescence with the manifestations of giftedness was the place of reflection of personalities in the process of settlement and management of their own habits and experience that underpins their talent and enhances the last. As a result, it was confirmed that the hypothesis of the existence of different prevailing values in the group of gifted young people and the control group. Here was confirmed the idea that the externally-directed actions that aim to achieve the welfare of others are inherent to a greater extent gifted individuals who have significant potential and are able to organize themselves and reflect their activities in accordance with their own values.
Keywords: reflectivity; young age; leading activity; motivation; giftedness of the individual; value orientation of the individual